Predictors of Morbidity and Mortality After Colorectal Surgery in Patients With Cirrhotic Liver Disease–A Retrospective Analysis of 54 Cases at a Tertiary Care Center - van Beekum, Cornelius J.; Beckmann, Christina; Semaan, Alexander; Manekeller, Steffen; Matthaei, Hanno; Braun, Lara; Willis, Maria A.; Kalff, Jörg C.; Vilz, Tim O. (Frontiers in Medicine, 2022)
Background: Despite various existing scores predicting morbidity and mortality of patients with cirrhotic liver disease (CLD), data on specific risk stratification of patients with CLD undergoing colorectal surgery (CRS) are rare. Aim of this study was to assess in hospital morbidity and mortality of patients with liver cirrhosis scheduled for CRS, with specific focus on possible pitfalls of surgery in this special cohort. Methods: Between 1996 and 2018, 54 patients with CLD undergoing CRS were identified and included into this study cohort. Postoperative morbidity and mortality using the Clavien/Dindo (C/D) classification as well as type of complication were assessed. Univariate and multivariate analysis was performed to analyze predictive factors for increased postoperative morbidity. Results: 37% of patients died during the procedure or postoperatively. Major complications were seen in 23.1% of patients (>C/D IIIb). Patients with Child B or C cirrhosis as well as patients undergoing emergency surgery experienced significantly more major complications (p=0.04, and p=0.023 respectively). The most common complications were bleeding requiring blood transfusion (51.1%) and cardiocirculatory instability due to bleeding or sepsis (44.4%). In 53.7% of patients an anastomosis was created without a protective ostomy. Anastomotic leakage occurred in 20.7% of these patients. Multivariate analysis showed that a primary anastomosis without a protective ostomy was the strongest risk factor for major complications (p=0.042). Discussion: Morbidity and mortality after CRS in patients with CLD remains high and is not only influenced by liver function but also by surgical variables. Considering the high rate of anastomotic leakage, creating a protective or definitive ostomy must be considered with regards to the underlying pathology, the extend of CLD and the patient’s condition. Moreover, our data suggest, that surgery in these most fragile patients should be performed only in experienced centers with immediate contact to hepatologists and hemostaseologists.